Analisis Kinerja Perusahaan melalui Analisis Dupont pada PT. Tjiwi Kimia Tbk - Sindy Larasasti; Putri Utami Permata Sari; Suci Ramadhani; Fitri Yani Panggabean (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research was conducted to analyze and understand the performance of the company PT Tjiwi Kimia Tbk with the Dupont system as an analytical tool. The data used in this study are secondary data, namely the company’s financial statements sourced through the IDX with the observation period 2020-2024. In the analysis conducted, it was found that the performance of the company PT Tjiwi Kimia in 2020-2024 was not good. This is because although the company showed a good ability to manage sales profitability (NPM) in several years and control the use of good debt (declining EM), the lack of efficient use of assets hindered the company’s ability to generate optimal returns for shareholders which resulted in a low ROE value. In signaling theory, a declining Equity Multiplier trend indicates a positive signal to investors regarding prudent debt management and more controllable financial risks. However, the low ROE value indicates a negative signal that the company needs to improve to increase investor confidence in profitability prospects.